Describing decision bias in the newsvendor problem: A prospect theory model. (January 2019) - Vipin, B.; Amit, R.K.
Highlights: This work explains the decision bias in the newsvendor experimental studies. Our model captures the non-linear ordering behavior and the pull-to-center effect. Our model describes the heterogeneity in the individual newsvendor orders. Abstract: In the newsvendor setting, we consider a prospect theory model with a stochastic-subjective reference point. The reference point is based on the pay-offs corresponding to the extreme values of demand; and, is influenced by the perception of costs associated with understocking and overstocking, and the pessimism level of the decision maker. Our prospect theory model describes the recent observations in the newsvendor experiments—the non-linear ordering behavior with respect to the profit margin and behavior at the extreme profit margins, in addition to the pull-to-center effect and asymmetry in ordering.